Study on Mechanical Behavior of Fully Encased Composite Slender Columns with High-Strength Concrete Using FEM Simulation - Getinet Melesse; Samuel Jima; Tegegn Asale; Yayesew Moges; Hibretu Kaske Kassa (Advances in Civil Engineering)
The most common types of composite columns used in high-rise structures are concrete-filled steel tubes (CFSTs) and concrete-encased steel (CES) that are either entirely or partially encased in concrete. The attempt of this study is to develop a suitable constitutive model addressing the behavior of fully encased composite slender columns with high-strength concrete subjected to axial loading. The nonlinear finite element (FE) package ABAQUS version 6.14-2 is used to study the response of fully encased composite (FEC) slender columns. The finite element analysis (FEA) results are validated with experimental data extracted from previous experiments. Then, the parametric study is conducted on rectangular FEC columns with different shapes of encased steel encasements to investigate the axial load-carrying capacities, axial deformation, ductility, load-deformation behavior, and confinement of FEC columns. The governing parameters for the current study are the high strength of concrete (90 MPa, 100 MPa, and 120 MPa), shapes of encased steel sections (circular, I-shaped, and rectangular steel encasements), and spacing of tie bars (50 mm, 100 mm and 150 mm). 6–21% of load increment is observed by changing the concrete compressive strength. A comparison is also made between the results of reinforced concrete and FEC slender columns and 2–11% of load increment is recorded by changing the shape of structural steel and keeping other parameters constant. The results of calibrated finite element models revealed that closely spaced tie bars resulted in a good ductility of FEC column with high-strength concrete (HSC). Significant enhancements in the axial load capacity are observed in the case of FEC slender columns than in RC slender columns of the same size and shape. Ductility and residual strength after the failure of FEC columns are also observed to increase significantly with the adoption of tubular structural steel sections. However, increasing the concrete strength results in the reduction of this ductility.